2009
DOI: 10.1016/j.ajhg.2009.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Deletions and Point Mutations of LRRC50 Cause Primary Ciliary Dyskinesia Due to Dynein Arm Defects

Abstract: Genetic defects affecting motility of cilia and flagella cause chronic destructive airway disease, randomization of left-right body asymmetry, and, frequently, male infertility in primary ciliary dyskinesia (PCD). The most frequent defects involve outer and inner dynein arms (ODAs and IDAs) that are large multiprotein complexes responsible for cilia-beat generation and regulation, respectively. Here, we demonstrate that large genomic deletions, as well as point mutations involving LRRC50, are responsible for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 19 publications
(29 reference statements)
5
159
1
4
Order By: Relevance
“…Interestingly Immunofluorescent antibodies revealed the presence of the IDA component protein DNALI1 in all these patients. This is in contrast to combined ODA and IDA defects caused by KTU and LRRC50 mutations as well as in respiratory cilia characterized by combined dynein regulatory complex (DRC)/IDA defects caused by CCDC39 and CCDC40 mutations, where DNALI1 is absent respectively [15][16][17][18]. This immunofluorescence finding confirms that at least a subset of IDAs can be assembled in these cases and excludes a complete IDA absence explaining difficulties at TEM.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly Immunofluorescent antibodies revealed the presence of the IDA component protein DNALI1 in all these patients. This is in contrast to combined ODA and IDA defects caused by KTU and LRRC50 mutations as well as in respiratory cilia characterized by combined dynein regulatory complex (DRC)/IDA defects caused by CCDC39 and CCDC40 mutations, where DNALI1 is absent respectively [15][16][17][18]. This immunofluorescence finding confirms that at least a subset of IDAs can be assembled in these cases and excludes a complete IDA absence explaining difficulties at TEM.…”
Section: Discussionsupporting
confidence: 52%
“…The identification of genes regulating cilia formation and function is the key first step towards understanding the biology of cilia and ciliopathies. Despite the fact that PCD ranks among the most prevalent of ciliopathies, causative mutations in a limited number of genes have been discovered, mainly in those encoding axonemal dynein subunits (Bartoloni et al, 2002;Loges et al, 2008;Mazor et al, 2011;Olbrich et al, 2002;Pennarun et al, 1999) and dynein motor assembly proteins (Kott et al, 2012;Loges et al, 2009;Mitchison et al, 2012;Omran et al, 2008). These mutations account for fewer than two-thirds of the total cases of PCD (Zariwala et al, 2011), indicating that a large number of motile cilia genes whose mutations cause PCD have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…For nNO validation studies at six (non-UNC) sites, PCD was confirmed by PCD-specific ciliary EM defects and, by the presence of biallelic mutations in PCD genes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Informed consent was obtained at the University of North Carolina at Chapel Hill and collaborating institutions under the auspices of Committees on the Protection of the Rights of Human Subjects.…”
Section: Original Researchmentioning
confidence: 99%